Poisoning Cases’ Demographic Profile in Accordance to an Observational Study of a Tertiary Care Center in South India - J, James Rajesh; P, Sampath Kumar; A, Jothi Marie Feula (Medicine and Medical Research: New Perspectives Vol. 8, 2024)
In the Middle Ages, the physician/alchemist Paracelsus (1493–1541) claimed that in the world, there is no substance in the world that is entirely non-toxic; rather, the therapeutic and toxic effects of substances are indistinguishable except for one critical factor—dose. The word "poison" originated from the Latin word "potion," which meant "to drink for health." However, over time, the meaning of "poison" shifted irreversibly to include any substance that has the potential to harm a person's body when given, inhaled, or consumed. This chapter helps to identify the demographics of poisoning cases that were reported to a tertiary care institute. Here, 353 instances of poisoning that were admitted to Sri Ramachandra Medical College & Research Institute, Sri Ramachandra University, Porur, Chennai, India between June 2014 and June 2015 were studied in this chapter. All the data collected in the Performa were compiled and analyzed statistically using SPSS software version 15. The age range of 20 to 29 years old had the highest number of poisoning cases. The incidences of cases gradually increased with the increase in the age range. It was obvious that poisoning occurred more frequently in females than in males. According to the distribution of occupations, poisoning was more common among skilled workers, accounting for 167 occurrences. According to socioeconomic position, poisoning was most common among upper middle class individuals (52%), with middle class individuals accounting for 33% of instances. When compared to single persons, married individuals experienced poisoning more frequently. Of the 353 instances, 203 (or 58% of the total) were married, and 150 (or 48% of the cases) were single. A breakdown of the research population by family type showed that 299 of the 353 cases overall belonged to nuclear families. Individuals that are part of a joint family were 46 in total.